High-thermal-conductivity capsule and preparation method thereof

Through reasonable material ratio, high thermal conductivity vulcanized capsules were prepared, which solved the problem of insufficient thermal conductivity in the prior art, achieved higher thermal conductivity and lower production costs, and met higher consistency and quality requirements of finished products.

CN119552454APending Publication Date: 2025-03-04JIAXING XINSHENG RUBBER MOLD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411591094.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The thermal conductivity of existing high-thermal vulcanized capsules is no longer able to meet the needs of advanced manufacturing processes, resulting in a bottleneck in heat transfer speed, affecting the uniformity of the vulcanization and overall performance of the tire.

Method used

Through reasonable material ratios, high thermally conductive vulcanized capsules are prepared by using conventional low-cost materials such as butyl glue, acetylene black, zinc oxide, N220 carbon black, oil, silicon carbide, chloroprene, vulcanized resin and stearic acid to avoid the use of high-cost graphene.

Benefits of technology

It significantly improves the thermal conductivity of vulcanized capsules, reduces production costs, and ensures the stability and durability of the capsules in high temperature and high load environments, meeting higher consistency and quality requirements for finished products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552454A_ABST
    Figure CN119552454A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of tires, in particular to a high-thermal-conductivity capsule and a preparation method thereof.The preparation method comprises the steps that 100 parts of butyl rubber, 4-6 parts of zinc oxide and 5-25 parts of silicon carbide are weighed and put into an internal mixer to be subjected to primary mixing for 55 seconds, after primary mixing is completed, 55-65 parts of acetylene black and 5-10 parts of N220 carbon black are added into the mixture, mixing continues to be conducted for 60 seconds, and the high-thermal-conductivity capsule is obtained; the preparation method comprises the following steps: adding a rubber material into an internal mixer to ensure that carbon black is fully dispersed in the rubber material, adding 5-7 parts of oil into the mixture, mixing for 55 seconds, cleaning, continuously mixing for 60 seconds, finally adding 3-5 parts of chloroprene rubber adhesive, 6-10 parts of vulcanized resin and 0.3 part of stearic acid into the internal mixer together, and mixing for 125 seconds at the temperature of 120 DEG C. According to the invention, the conventional materials with low cost and proportioning combination are adopted, so that the rubber material is prepared; the use of high-cost graphene is avoided, and the production cost is remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of tires, and more particularly to a high thermal conductivity capsule and a preparation method thereof. Background Art

[0002] Curing bladders are essential auxiliary materials for tire production. During the tire vulcanization process, medium energy is transferred to the tire through the curing bladder, providing the heat required for vulcanization while ensuring that the tire has a reasonable inner contour shape; the thermal conductivity of the curing bladders commonly used in tire factories is usually around 0.260. With the improvement of product quality and production efficiency requirements, the market demand for high thermal conductivity curing bladders is gradually increasing. The current high thermal conductivity bladder thermal conductivity is between 0.300 and 0.420. Although high thermal conductivity bladders have significantly improved vulcanization efficiency, they still cannot fully meet the increasingly stringent manufacturing requirements, such as shorter vulcanization time, higher finished product consistency and quality.

[0003] Although the existing high thermal conductivity curing bladder can improve the heat conduction performance in application, with the complexity of tire design and the continuous improvement of production efficiency, the upper limit of its thermal conductivity coefficient (0.420) has been difficult to meet the needs of advanced manufacturing processes. The bottleneck of heat transfer speed not only limits the uniformity of tire vulcanization, but also may cause excessive local temperature differences, thus affecting the overall performance and service life of the tire.

[0004] Therefore, further improving the thermal conductivity of the vulcanization bladder is the key to breaking through the bottleneck of existing technology.

[0005] For example, announcement number CN108162226A discloses a method for preparing a high thermal conductivity tire curing bladder, the materials used are: Butyl rubber 95, chloroprene rubber 4-5, N375 carbon black 15-20, acetylene carbon black 35-45, graphene 7-15, alkane oil 7-10, stearic acid 0.5-1.5, zinc oxide 5-7, resin 8-10, The use of butyl rubber and acetylene black is reduced by setting graphene, and the addition of graphene in the high thermal conductivity tire curing bladder formula makes this curing bladder not only have high thermal conductivity, but also have excellent physical and mechanical capabilities and service life. According to the test data implemented in this technology, through the above formula and the process flow for processing, the thermal conductivity of the curing bladder obtained reaches 0.4482 and 0.4572.

[0006] The above-mentioned prior art uses graphene to further improve the thermal conductivity of the vulcanization capsule, but the preparation cost of graphene is very high, which increases the cost. Although the addition of graphene can enhance thermal conductivity, it will affect the toughness and strength of the material, resulting in embrittlement of the material.

[0007] Based on the existing problems, it is an important task to increase the thermal conductivity of the molded vulcanization bladder by using a combination of conventional low-cost materials and proportions. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high thermal conductivity vulcanization bladder with higher thermal conductivity, excellent physical and mechanical properties and low cost. Specifically, the present invention solves the economic burden problem caused by the use of high-cost materials (such as graphene) in the prior art through a reasonable material ratio, while ensuring the stability and durability of the vulcanization bladder under high temperature and high load environments.

[0009] To achieve the above object, the present invention provides the following technical solutions: A high thermal conductivity capsule comprises the following raw materials: butyl rubber, acetylene black, zinc oxide, N220 carbon black, oil, silicon carbide, chloroprene rubber, vulcanized resin and stearic acid.

[0010] The present invention is further configured as follows: the raw materials include, by weight: 100 parts of butyl rubber, 55-65 parts of acetylene black, 4-6 parts of zinc oxide, 5-10 parts of N220 carbon black, 5-7 parts of oil, 5-25 parts of silicon carbide, 3-5 parts of chloroprene rubber, 6-10 parts of vulcanized resin, and 0.3 parts of stearic acid.

[0011] The present invention is further configured as follows: the raw materials include, by weight: 100 parts of butyl rubber, 60-65 parts of acetylene black, 5-6 parts of zinc oxide, 7-10 parts of N220 carbon black, 6-7 parts of oil, 10-25 parts of silicon carbide, 4-5 parts of chloroprene rubber, 8-10 parts of vulcanized resin, and 0.3 parts of stearic acid.

[0012] A method for preparing a high thermal conductivity capsule comprises the following steps: Step 1: Weigh the butyl rubber, zinc oxide and silicon carbide, put them into an internal mixer and mix them for 55 seconds to ensure that the ingredients are evenly dispersed; After the initial mixing is completed, acetylene black and N220 carbon black are added to the mixture and mixing is continued for 60 seconds to ensure that the carbon black is fully dispersed in the rubber; Add the oil to the mixture and mix for 55 seconds. After the top bolt is cleaned, continue mixing for 60 seconds. The temperature during mixing was controlled at 175°C. Step 2: Add the rubber obtained in step 1, chloroprene rubber, vulcanized resin and stearic acid into an internal mixer and mix for 125 seconds at a temperature of 120°C.

[0013] Compared with the shortcomings of the prior art, the beneficial effects of the present invention are: The conventional low-cost materials and proportion combination are used to avoid the use of high-cost graphene, significantly reducing the production cost. At the same time, the thermal conductivity exceeds the thermal conductivity coefficient obtained by using graphene in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0015] Reference Figure 1 The embodiments of the present invention are further described.

[0016] A high thermal conductivity capsule comprises the following raw materials: butyl rubber, acetylene black, zinc oxide, N220 carbon black, oil, silicon carbide, chloroprene rubber, vulcanized resin and stearic acid.

[0017] Example 1: The raw materials include, by weight: 100 parts of butyl rubber, 65 parts of acetylene black, 4 parts of zinc oxide, 5 parts of N220 carbon black, 5 parts of oil, 5 parts of silicon carbide, 5 parts of chloroprene rubber, 6 parts of vulcanized resin, and 0.3 parts of stearic acid.

[0018] Example 2: 100 parts of butyl rubber, 65 parts of acetylene black, 6 parts of zinc oxide, 10 parts of N220 carbon black, 7 parts of oil, 25 parts of silicon carbide, 5 parts of chloroprene rubber, 10 parts of vulcanized resin, and 0.3 parts of stearic acid.

[0019] Example 3: The raw materials include, by weight: 100 parts of butyl rubber, 60 parts of acetylene black, 5 parts of zinc oxide, 7 parts of N220 carbon black, 6 parts of oil, 10 parts of silicon carbide, 4 parts of chloroprene rubber, 8 parts of vulcanized resin, and 0.3 parts of stearic acid.

[0020] Example 4: The raw materials include, by weight: 100 parts of butyl rubber, 57 parts of acetylene black, 4 parts of zinc oxide, 6 parts of N220 carbon black, 6 parts of oil, 8 parts of silicon carbide, 4 parts of chloroprene rubber, 7 parts of vulcanized resin, and 0.3 parts of stearic acid.

[0021] Comparative Example 1: The raw materials include, by weight: 100 parts of butyl rubber, 66 parts of acetylene black, 7 parts of zinc oxide, 11 parts of N220 carbon black, 8 parts of oil, 26 parts of silicon carbide, 6 parts of chloroprene rubber, 11 parts of vulcanized resin, and 0.3 parts of stearic acid.

[0022] Comparative Example 2: The raw materials include, by weight: 100 parts of butyl rubber, 54 parts of acetylene black, 3 parts of zinc oxide, 4 parts of N220 carbon black, 4 parts of oil, 4 parts of silicon carbide, 2 parts of chloroprene rubber, 5 parts of vulcanized resin, and 0.3 parts of stearic acid.

[0023] Comparative Example 3: The raw materials include, by weight: 100 parts of butyl rubber, 70 parts of acetylene black, 10 parts of zinc oxide, 15 parts of N220 carbon black, 10 parts of oil, 30 parts of silicon carbide, 8 parts of chloroprene rubber, 15 parts of vulcanized resin, and 0.3 parts of stearic acid.

[0024] Comparative Example 4: The raw materials include, by weight: 100 parts of butyl rubber, 50 parts of acetylene black, 1 part of zinc oxide, 2 parts of N220 carbon black, 2 parts of oil, 2 parts of silicon carbide, 1 part of chloroprene rubber, 2 parts of vulcanized resin, and 0.3 parts of stearic acid.

[0025] According to Example 1-Example 4 The method for preparing the high thermal conductivity capsules outputted by the raw material ratios in Comparative Examples 1 to 4 comprises the following steps: Step 1: Weigh butyl rubber, zinc oxide and silicon carbide, put them into an internal mixer and mix them for 55 seconds to ensure that the materials are evenly dispersed; After the initial mixing is completed, acetylene black and N220 carbon black are added to the mixture and mixing is continued for 60 seconds to ensure that the carbon black is fully dispersed in the rubber; Add the oil to the mixture and mix for 55 seconds. After the top bolt is cleaned, continue mixing for 60 seconds. The temperature during the mixing was controlled at 175°C.

[0026] Step 2: Add the rubber obtained in step 1, chloroprene rubber, vulcanized resin and stearic acid into an internal mixer and mix for 125 seconds at a temperature of 120°C.

[0027] The product testing data obtained above are as follows:

[0028] Based on the comparison of the embodiments and comparative examples: Examples 1-4: The usage range of acetylene black is 55-65 parts (55 in Example 1, 65 in Example 2, 60 in Example 3, and 57 in Example 4).

[0029] Comparative Examples 1-4: The usage of acetylene black is relatively high (such as 66 in Comparative Example 1 and 70 in Comparative Example 3), or relatively low (such as 54 in Comparative Example 2 and 50 in Comparative Example 4).

[0030] In the comparative examples where the acetylene black content is relatively high (Comparative Examples 1 and 3), although the thermal conductivity coefficient is improved, the flexibility and processing performance of the material are reduced, and the tensile strength is weakened.

[0031] In the comparative examples with low acetylene black content (Comparative Examples 2 and 4), the thermal conductivity coefficient decreases, especially when the content of silicon carbide is low, the overall thermal conductivity coefficient will be greatly affected.

[0032] Example 1-4: The usage range of silicon carbide is 5-25 parts (5 in Example 1, 25 in Example 2, 10 in Example 3, and 8 in Example 4).

[0033] Comparative Examples 1-4: The amount of silicon carbide used in most comparative examples is relatively high (such as 26 in comparative example 1 and 30 in comparative example 3), or very low (such as 4 in comparative example 2 and 2 in comparative example 4).

[0034] In the comparative examples with higher silicon carbide content (Comparative Examples 1 and 3), the thermal conductivity coefficient is improved, but because silicon carbide is a rigid material, a higher content will weaken the ductility of the material, resulting in a decrease in tensile strength and elongation at break.

[0035] In the comparative examples with lower silicon carbide content (Comparative Examples 2 and 4), the thermal conductivity coefficient is seriously affected, especially in Comparative Example 4, where the silicon carbide content is only 2 parts, which cannot effectively improve the thermal conductivity.

[0036] Examples 1-4: The usage range of N220 carbon black is 5-10 parts (5 parts in Example 1, 10 parts in Example 2, 7 parts in Example 3, and 6 parts in Example 4).

[0037] Comparative Examples 1-4: The usage of N220 carbon black is relatively high (such as 11 in Comparative Example 1 and 15 in Comparative Example 3), and there is a small amount (such as 4 in Comparative Example 2 and 2 in Comparative Example 4).

[0038] A higher proportion of N220 carbon black (such as Comparative Examples 1 and 3) will enhance the strength and hardness of the material, but too high a proportion will reduce the flexibility of the material.

[0039] The comparative examples with low N220 carbon black content (Comparative Examples 2 and 4) will result in insufficient material strength and wear resistance, thereby reducing the overall mechanical properties.

[0040] Embodiment 1-4: The usage range of oil is 5-7 parts (5 in embodiment 1, 7 in embodiment 2, 6 in embodiment 3, and 6 in embodiment 4).

[0041] Comparative Examples 1-4: The amount of oil used is sometimes higher (e.g., 8 in Comparative Example 1, 10 in Comparative Example 3), or less (e.g., 4 in Comparative Example 2, 2 in Comparative Example 4).

[0042] Too high an oil content (such as in Comparative Examples 1 and 3) would reduce the hardness and strength, resulting in excessive softening of the capsule.

[0043] If the oil content is too low (such as in Comparative Examples 2 and 4), the material will have insufficient elasticity, thus affecting its service life and fatigue resistance.

[0044] The hardness (HD), tensile strength (TS), modulus modulus (300% MOD) and elongation at break (Elong) of Examples 1-4 are relatively balanced, especially Example 2 which performs well in tensile strength, modulus modulus and hardness.

[0045] In the comparative examples, especially comparative example 3, although the hardness and tensile strength are higher, the elongation at break is significantly lower than that of the examples, indicating that the flexibility is poor and the capsule is easily brittle.

[0046] The thermal conductivity coefficients of Examples 1-4 are generally high, especially Example 2 (0.550 W / mk), which is significantly better than the comparative examples. Among the comparative examples, Comparative Examples 2 and 4 have relatively low thermal conductivity coefficients.

[0047] Examples 1-4 performed well in terms of the number of times of tire vulcanization use, especially Example 2 which reached 430 times, showing its excellent comprehensive performance.

[0048] In the comparative examples, especially comparative example 4, the tire vulcanization use times are significantly lower, indicating that its durability and fatigue resistance are insufficient.

[0049] By comparing and analyzing the ingredients and performance data of the examples and comparative examples, the following conclusions can be drawn: Example 2 is the optimal formula. It performs well in thermal conductivity, mechanical properties and service life, especially high tensile strength, elongation at break and long service life, and is suitable for use in scenarios with high thermal conductivity and high durability requirements.

[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Common changes and substitutions made by those skilled in the art within the scope of the technical solution of the present invention should be included in the protection scope of the present invention.

Claims

1. A high thermal conductivity capsule, characterized in that: It includes the following raw materials: butyl rubber, acetylene black, zinc oxide, N220 carbon black, oil, silicon carbide, chloroprene rubber, vulcanized resin and stearic acid.

2. A high thermal conductivity capsule according to claim 1, characterized in that: The raw materials include, by weight: 100 parts of butyl rubber, 55-65 parts of acetylene black, 4-6 parts of zinc oxide, 5-10 parts of N220 carbon black, 5-7 parts of oil, 5-25 parts of silicon carbide, 3-5 parts of chloroprene rubber, 6-10 parts of vulcanized resin, and 0.3 parts of stearic acid.

3. A high thermal conductivity capsule according to claim 2, characterized in that: The raw materials include, by weight: 100 parts of butyl rubber, 60-65 parts of acetylene black, 5-6 parts of zinc oxide, 7-10 parts of N220 carbon black, 6-7 parts of oil, 10-25 parts of silicon carbide, 4-5 parts of chloroprene rubber, 8-10 parts of vulcanized resin, and 0.3 parts of stearic acid.

4. The method for preparing the high thermal conductivity capsule according to claims 1-3, characterized in that: The steps include: Step 1: Weigh the butyl rubber, zinc oxide and silicon carbide and put them into an internal mixer for preliminary mixing for 55 seconds to ensure that the two are evenly dispersed; After the initial mixing is completed, acetylene black and N220 carbon black are added to the mixture and mixing is continued for 60 seconds to ensure that the carbon black is fully dispersed in the rubber; Add the oil to the mixture and mix for 55 seconds. After cleaning the top bolt on the internal mixer, continue mixing for 60 seconds. The temperature during mixing was controlled at 175°C. Step 2: add the rubber obtained in step 1, chloroprene rubber, vulcanized resin and stearic acid into an internal mixer after weighing, and mix for 125 seconds at a temperature of 120°C.

Citation Information

Patent Citations

  • Preparation method of high-heat-conductivity type tire vulcanization capsule

    CN108162226A